The role of sleep deficiency in the trajectory of postconcussive symptoms in adolescents. (19th September 2019) - Tham, See Wan; Aaron, Rachel V.; Palermo, Tonya M.
ABSTRACT: Objective : To investigate the trajectory of sleep deficiency after concussion and examine its role as a predictor of postconcussive symptoms (PCS) over 3 weeks and at 3 months post-concussion. Design : This was a prospective pilot study of 29 adolescents recruited from a pediatric Emergency Department (69% female, mean age = 14.0 years, SD = 1.8) following a concussion. Methods : Adolescents completed questionnaire assessments at baseline, Weeks 1, 2, and 3 on PCS and sleep patterns. Concurrently, adolescents also completed a daily diary and wore an actigraph continuously to monitor sleep activity. At 3 months post-concussion, adolescents repeated questionnaire measures. Results : At enrollment, 53.6% reported severe PCS, and 12% maintained severe symptoms at 3 months. Over the first 3 weeks, sleep duration and daytime sleepiness gradually declined; however, insomnia symptoms remained unchanged. After accounting for age, sex and time since concussion, greater insomnia symptoms at enrollment were associated with more severe PCS at 3 weeks and 3 months (β = 1.17, p < .001). In contrast, sleep duration, efficiency, and waketime after sleep onset were not predictors. Conclusions : Study findings suggest that insomnia symptoms after concussion may provide a target for early intervention to reduce prolonged severity and duration of PCS.